Psience Fiction: The Paranormal in Science Fiction Literature by Damien Broderick - Smith, Paul (Journal of Scientific Exploration, 2019)
Psience Fiction: The Paranormal in Science Fiction Literature is a book that really needed to be written. In an abundance of hubris I once played with the idea myself (and I was probably not alone in the thought). But now Damien Broderick has done it, and much better than I could have even approximated. Given his background as a science fiction literary critic and author himself, no other writer could be better-equipped. Psience Fiction is exactly the right title to encapsulate Broderick’s chosen topic. As he notes in one passage, his purpose here is to explore “the varied representations of the paranormal in science fiction” (p.68)–though by paranormal he refers neither to ghosts nor mediumship nor UFO-related phenomena, but strictly to “paranormal” as it relates to putative mental powers that transcend the scientifically-presumed, neuro-physical limits of our minds and brains. He refines that still further in noting that what he wants to consider is “...the give and take between the science fiction paranormal and the real-world kind, tested and tallied by psi researchers” (p.5). This book is probably most easily described as a book of book reviews (though a few relevant short stories are also considered). Authors covered run the gamut from Olaf Stapledon, E.E. “Doc” Smith, James Blish and Theodore Sturgeon to Zenna Henderson, John Wyndham, Robert Heinlein, Ann McCaffery, Octavia Butler, and John Brunner, plus many more. For a literary work to be included, it must incorporate some aspect of psi as an integral plot element; a mere mention of extrasensory perception or psychokinesis does not suffice.